Energy Generation: A Review - Jain, Nirupa; Kumar, Krishan; Sharma, Anshumala; Sangwa, Narpat Ram (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 6 No 3&4 (2019): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The society is facing the problem relating to energy. The researchers look at the present crisis and identify different sources of energy. This is a review of important research papers on the subject of energy generation. Energy includes electricity and other forms of energy which enables mankind in its activities. Energy generation refers to generation of electricity from primary sources of power. Energy sources include renewable and non-renewable sources. Renewable sources include those sources, which are non-perishable and therefore these sources of energy should be promoted. These sources include the following: • Hydro-electric – energy generated from dams and reservoirs • Solar energy – energy generated through Rays of the Sun • Wind power energy - energy generated through wind • Tidal energy – electricity generated through tides • Bio-fuel – electricity generated from lifeless biological material • Geothermal energy – it is the energy derived from internal structure of the Earth • Non-renewable sources of energy include all those sources of energy, which will exhaust and therefore they have a limited supply. These include nuclear energy, fossil fuel, SDG7 refers to sustainable development goal of providing an access to clean, sustainable and economical source of energy to everyone. Electrification refers to the use of electricity in using some equipment or for other uses or applications. How to cite this article: Jain N, Kumar K, Sharma A et al. Energy Gen- eration: A Review. J Adv Res Alt Energ Env Eco 2019; 6(3&4): 29-33.